Changes in Symbiotic Microbiota and Immune Responses in Early Development Stages of Rapana venosa (Valenciennes, 1846) Provide Insights Into Immune System Development in Gastropods - Yang, Mei-Jie; Song, Hao; Yu, Zheng-Lin; Hu, Zhi; Zhou, Cong; Wang, Xiao-Long; Zhang, Tao (Frontiers in Microbiology, 2020)
The symbiotic microbiota can stimulate modulation of immune system, which also can promote immune system mature in critical developmental periods. In this study, we have investigated the symbiotic microbiota in Rapana venosa at five early development stages using Illumina high-throughput sequencing, and detected immune responses in larvae. Analysis of the symbiotic microbiota sequences identified that the most abundant phylum was Proteobacteria. Beta diversity analysis indicated that the structure of the symbiotic microbiota dramatically shifted in early development stages. The abundance of immune-related KEGG Orthologs (KOs) also increased in competent larval (J4, 30-day post-hatching) and postlarval after three days of metamorphosis (Y5, 33-day post-hatching) stages. Acid phosphatase activity decreased significantly in the Y5 stage, and alkaline phosphatase activity also at a lower level in Y5 stage, whereas lysozyme activities exhibited no remarkable change. Also, the activities of catalase and superoxide dismutase activities decreased dramatically during early development stages of R. venosa. Dramatic changes in the symbiotic microbiota and the immune response mainly occurred in the initially hatched veliger (C1), competent larval (J4) and postlarval (Y5) stages, during which the hosts might experience substantial environmental changes or changes in physiological structure and function. These findings expand our understanding of the stage-specific symbiotic microbiota in R. venosa and the close association between immune system and symbiotic microbiota in mollusks, however, the specific relationship may need more researches are needed to investigated in the future.